2007
DOI: 10.1080/15374410701651637
|View full text |Cite
|
Sign up to set email alerts
|

Girl Friend, Boy Friend, Girlfriend, Boyfriend: Broadening our Understanding of Heterosocial Competence

Abstract: Heterosocial interactions, or social interactions with other-sex peers, are theorized to serve a number of unique developmental functions for adolescents (e.g., companionship, intimacy, experimentation with sex-role behaviors and sexual activity). Yet despite the importance of heterosocial competence in adolescent social development, there exists little research on the construct. Early research, although informative, reflects a narrow focus on heterosocial anxiety associated with date initiation situations. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 48 publications
1
31
5
Order By: Relevance
“…The gender of one's friend has been related to friendship experiences, includ ing the promotion of psychosocial adjustment (Grover et al, 2007). However, it was surprising that our study found that men with same gender friends reported higher levels of friendship quality (including intimate disclosure) than those with other gender friends, because their friendships with women are typically more intimate than their friendships with men (Roy et al, 2000).…”
Section: Friend's Gender and Psychosocial Adjustmentcontrasting
confidence: 51%
See 2 more Smart Citations
“…The gender of one's friend has been related to friendship experiences, includ ing the promotion of psychosocial adjustment (Grover et al, 2007). However, it was surprising that our study found that men with same gender friends reported higher levels of friendship quality (including intimate disclosure) than those with other gender friends, because their friendships with women are typically more intimate than their friendships with men (Roy et al, 2000).…”
Section: Friend's Gender and Psychosocial Adjustmentcontrasting
confidence: 51%
“…Although the current study found that women reported higher levels of self esteem, the literature was mixed with some finding lower levels (Orth, Trzesniewski, & Robins, 2010) and others finding higher levels (Grover et al, 2007) for women. Further, these gender differences tended to diminish only after the age of 30 (Orth et al, 2010).…”
Section: Gender and Psychosocial Adjustmentcontrasting
confidence: 40%
See 1 more Smart Citation
“…Although the current study found that women reported higher levels of selfesteem, the literature was mixed with some finding lower levels (Orth, Trzesniewski, & Robins, 2010) and others finding higher levels (Grover et al, 2007) for women. Further, these gender differences tended to diminish only after the age of 30 (Orth et al, 2010).…”
Section: Gender and Psychosocial Adjustmentcontrasting
confidence: 40%
“…Specifically, a steady increase of selfesteem occurs from ado lescence to middle adulthood, when thereafter it declines (Orth, Robins, & Widaman, 2012). Reports of gender differences have been mixed, with some studies reporting emergingadult women as having lower levels of selfesteem (Galambos, Barker, & Krahn, 2006), and other studies reporting higher levels of selfesteem (Grover et al, 2007) compared to emergingadult men. Given that selfesteem has been shown to decrease when individuals face multiple transitions (e.g., early adolescent girls who experience simultaneous pubertal and school transitions; Simmons & Blyth, 1987), it is important to study selfesteem in emerging adulthood, a time of instability in social networks (Arnett, 2011).…”
Section: Other-gender and Same-gender Friendshipsmentioning
confidence: 92%